Estimated risk of cancer transmission from organ donor to graft recipient in a national transplantation registry. Issue 7 (28th April 2014) - Desai, R.; Collett, D.; Watson, C. J. E.; Johnson, P.; Evans, T.; Neuberger, J.
<x xml:space="preserve">Abstract</x> Background Transplanted organs carry the risk of inadvertent donor cancer transmission. Some cancers in organ donors have been classified as being associated with a high or unacceptable risk, but the evidence for such recommendations is scanty. Methods The risk of cancer transmission from donors characterized as high or unacceptable risk was studied by analysing transplant and cancer registry data. Donors and recipients from England (1990–2008) were identified from the UK Transplant Registry. Cancer details were obtained from cancer registries and classified using guidelines from the Council of Europe and Organ Procurement and Transplantation Network/United Network for Organ Sharing. Results Of 17 639 donors, 202 (1·1 per cent) had a history of cancer, including 61 donors with cancers classed as having an unacceptable/high risk of transmission. No cancer transmission was noted in 133 recipients of organs from these 61 donors. At 10 years after transplantation, the additional survival benefit gained by transplanting organs from donors with unacceptable/high‐risk cancer was 944 (95 per cent confidence interval (c.i.) 851 to 1037) life‐years, with a mean survival of 7·1 (95 per cent c.i. 6·4 to 7·8) years per recipient. Conclusion Strict implementation of present guidelines is likely to result in overestimation of cancer transmission risk in some donors. Organs from some donors with cancers defined as unacceptable/high risk can be used safely.